Social media use as a coping mechanism during the COVID-19 pandemic: A multidimensional perspective on adolescents' well-being - Maftei, Alexandra; Merlici, Ioan-Alex; Dănilă, Oana (Frontiers in Public Health, 2023)
The present study explored how adolescents might use social media as a coping mechanism during the Covid-19 pandemic, using a multidimensional perspective on well-being. Our sample consisted of 259 Romanian teenagers aged 11 to 16 (M = 13.38, SD = .93, 57% males). We investigated the potential indirect effect of social media use, i.e., its cognitive, affective, and behavioral dimensions on the relationship between depressive symptoms and adolescents’ well-being. Across all mediation analyses, our results suggested that social media use positively predicted adolescents' well-being. Given the multidimensional approach to both social media use and well-being, our findings suggested that adolescents’ well-being was predicted not only by actual social media use behaviors but also by cognitions related to the expectation of receiving gratification on social media and the intense affective states related to the desire to use social media. Also, our data suggested that adolescents with high levels of depressive symptoms might be more likely to capitalize on social media use and have expectations related to receiving approval from others in the context of social media use. We discuss our findings regarding their implications for adolescents’ well-being during challenging times, such as the COVID-19 pandemic.